VOT in different age ranges - Ravishankar KC (Journal of All India Institute of Speech and Hearing, 1970)
Voice Onset Time (VOT) is one of the parameters among the temporal aspect of speech, which indicates laryngeal function. VOT has been defined as "The Duration Between the Release of a Complete Articulatory Constriction or Burst Transient and the Onset of Phonation" (Lisker and Abramson, 1964, 1967). Studies have shown that the VOT values change with age. This study was conducted to find out the changes in VOT values with age in males and females of 4 to 10 years.